Comparison of the Antibacterial Activity of Cinnamon Bark Extract (Cinnamomum burmannii) Against the Growth of Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus - Sandrean Hanesta; Gilbert Lister; Evelyn Angie (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aimed to compare the antibacterial activity of ethanol extract of cinnamon bark (Cinnamomum burmannii) against the growth of Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus (MRSA). This experimental study employed a post-test only design using the agar diffusion method (Kirby–Bauer) at extract concentrations of 25%, 50%, 75%, and 100%, with ciprofloxacin as the positive control and distilled water as the negative control. Inhibition zones were measured after 24 hours of incubation and analyzed using one-way ANOVA. The results showed that cinnamon bark extract produced strong inhibition zones for both bacteria, with diameters ranging from 11.53–12.97 mm for S. aureus and 12.00–13.47 mm for MRSA, although still lower than the positive control. The antibacterial activity of the extract was slightly higher against MRSA than S. aureus. In conclusion, ethanol extract of cinnamon bark exhibits antibacterial potential against both S. aureus and MRSA. Bioactive compounds such as alkaloids, flavonoids, tannins, and saponins are suspected to contribute to this effectiveness, warranting further research to clarify the mechanism of action and evaluate its potential application as a natural antibacterial agent